Pengembangan Potensi Wisata Gastronomi Halal Di Kabupaten Cianjur - Muhamad Syahpril Riano; Caria Ningsih; Hilman Taufiq Abdilah (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Cianjur Regency is one of West Java's natural resource-rich districts. The purpose of this research is to inventory food and beverages, determine the attractiveness of halal gastronomic tourism in Cianjur Regency, and determine the extent of the Cianjur Regency government's development efforts. is demonstrating a halal gastronomic tour package. Qualitative and quantitative methods are used (mix method research). The data collection techniques used in this study were observation, questionnaires, and interviews. The results of this study were six food classifications, namely side dishes, sepinggan, snacks, souvenirs, chili sauce, and traditional drinks. Cianjur Regency had four major tourist attraction destinations. The government's efforts to develop gastronomic tourism have not been realized, as evidenced by the lack of a work program involving MUI. The Cianjur government is working to promote natural and historical tourism. The development of gastronomic tourism in Cianjur Regency is in Quadrant 1, and the strategy that must be used in this situation is to support an aggressive growth policy (Growth Oriented Strategy) and identify ten development strategies.